Penerapan Prinsip Good Governance dalam Layanan Pendidikan Nonformal di Dinas Pendidikan dan Kebudayaan Kabupaten Sidoarjo - Liya Yunita; Kristyan Dwijosusilo; Ika Devy Pramudiana (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This research intends to examine the application of good governance principles in non-formal education services at the Sidoarjo District Education and Culture Office, concentrating on accountability, transparency, participation, and institutional responsiveness. The study is based on the necessity for effective governance to guarantee quality, fairness, and efficiency in educational services reaching broader communities. A case study approach using qualitative methods was utilized, involving key informants like the head of the non-formal education division, managers of training centers, tutors, and students. Data were gathered via in-depth interviews, field observations, and documentation, then analyzed thematically to uncover implementation patterns and difficulties. The findings show that accountability has been reinforced through organized program assessments and reporting, whereas transparency has enhanced through improved access to public data. Nonetheless, coordination among agencies and the capacity of human resources continue to be major obstacles. Engagement and reactivity have demonstrated improvement, yet demand enhanced integration of digital systems. The research finds that effective good governance execution depends on the collaboration of policy, technology, and various stakeholders. Suggestions highlight the need for strengthening officials' capabilities and creating cohesive education information systems to foster more responsible and inclusive governance.